A study on prevalence of postpartum depression: a cross-sectional study using Edinburgh postnatal depression scale - R., Manjula; Badakali, Meenakshi; Megharaj, Priyanka C.; Mallapur, Ashalata; Mutalik, Narayan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Postpartum depression (PPD) is defined as a non-psychotic depressive episode that starts in the postpartum period, generally defined as the year after delivery. It has been suggested that about 50-80% of women suffer from baby blues after birth. The present study was conducted to determine the prevalence of postpartum depression using the Edinburgh postnatal depression scale. Methods: The study area chosen was the field practice area of urban health centre attached to department of community medicine, S. N. Medical College, Bagalkot, Karnataka. It was a cross-sectional study done during the period of January and June 2023. A predesigned proforma was used for obtaining the data. Data was entered in excel sheet and analysed using spss software. Results: Among the 165 mothers who were willing to participate in the study, 33 mothers i.e., 20% of them were at a major risk of developing post-partum depression. Our study showed significant association with poor socioeconomic status, complication during labour, mode of delivery, gender of the baby. The association between the gender of the baby and postpartum depression was statistically significant. Conclusions: Postpartum depression, as evident from the study, is a major public health problem which usually goes missed during the evaluation of mother and child’s health during mothers’ reproductive period. Hence women should be screened for potential risk factors and depressive symptoms during pregnancy and postpartum periods so that appropriate interventions, if needed, can be initiated in a timely fashion.